Metabolite profiles of epimedin C in rat plasma and bile by ultra‐performance liquid chromatography coupled with quadrupole‐TOF‐MS. (23rd May 2014) - Cui, Li; Sun, E.; Zhang, Zhenhai; Tan, Xiaobin; Xu, Fengjuan; Jia, Xiaobin
ABSTRACT Epimedin C is one of the major bioactive constituents of Herba Epimedii. In this study, the metabolite profiles of epimedin C in rat plasma and bile were qualitatively investigated, and the possible metabolic pathways of epimedin C were subsequently proposed. After oral administration of epimedin C at a single dose of 80 mg/kg, rat biological samples were collected and pretreated by protein precipitation. Then these pretreated samples were injected into an Acquity UPLC BEH C18 column and detected by ultra‐performance liquid chromatography/quadrupole‐time‐of‐flight mass spectrometry. In all, 12 metabolites were identified in the biosamples. Of these, eight, two from plasma and six from bile, are, to our knowledge, reported here for the first time. The results indicated that epimedin C was metabolized via desugarization, dehydrogenation, hydrogenation, dehydroxylation, hydroxylation, demethylation and glucuronidation pathways in vivo. Thus, this study revealed the possible metabolite profiles of epimedin C in rat plasma and bile. Copyright © 2014 John Wiley & Sons, Ltd.